Lost in Translation or a Work in Progress? Developing Desistance-Informed Youth Justice Practice in the Welsh Context. (19th November 2020) - Deering, John; Evans, Jonathan
Abstract: This article draws upon empirical research conducted within a Welsh Youth Offending Service (YOS) in 2017–2018. It captured staff responses to the introduction of AssetPlus, an assessment tool intended to complement a corresponding move to desistance-informed practice. Given that YOSs are now expected to develop practice underpinned by desistance theories, the article focuses on how desistance theories were interpreted and translated into one YOS. It was concluded that the introduction of the new practice model suffered from inadequate planning and AssetPlus assessment did little to enhance this shift. In an exercise in Utopianism, the views of practitioners and managers were sought on what constituted 'ideal' practice with children in conflict with the law. The researchers found some evidence of support for holistic child-centred social work practice that addressed contextual factors. The study was conducted with a small sample of practitioners and operational managers, involving seven semi-structured interviews, two focus groups (a total of eighteen respondents), case file analysis, document reading and observation. Given the size of the sample, the findings are not regarded as generalisable, but rather as raising important issues and pointers for further research.